PENYELESAIAN SENGKETA KONSUMEN MELALUI GUGATAN KELOMPOK - Bambang Sugeng Ariadi Subagyono (Yuridika, 2010)
A group of consumers who suffered losses from the use or the use of the product, whether goods or services may lawsuit Class Action, taking into account some with principles in the context of the submission and examination. Inspection mechanism should be adjusted in accordance with the provisions contained in the entire Supreme Court Rules No. 1 of 2002 on Class Action Procedures.